Efficient sky-blue emitting Pt(ii) complexes based on imidazo[1, 2-f]phenanthridine-containing tetradentate ligands. Issue 36 (7th September 2017) - Zhang, Wenjuan; Ma, Jie; Liu, Guo-Jun; Liu, Xiang-Yang; Fan, Jian; Liao, Liang-Sheng
Abstract : Three blue-emitting platinum(ii ) complexes based on imidazo[1, 2- f ]phenanthridine-containing tetradentate ligands have been prepared as efficient dopants for phosphorescent OLEDs. Abstract : Three blue-emitting Pt(ii ) complexes (Pt1, Pt2 andPt3 ) supported by imidazo[1, 2- f ]phenanthridine-containing tetradentate ligands have been designed and prepared. A fused ring system, imidazo[1, 2- f ]phenanthridine, was introduced into these complexes to minimize the vibration and rotation of the ligand due to its rigidity, and the incorporation of this robust motif led to the high thermal stability of the resulting complexes. In addition, this efficient bidentate possesses high triplet energy ( E T ) to allow the preparation of blue-emitting complexes. A bulky mesityl group was attached to this rigid unit to reduce the strong intermolecular interaction and suppress the formation of an excimer in the solid state. Imidazo[1, 2- f ]phenanthridine was connected with three different pyridine^benzene bidentates to give the corresponding tetradentate ligands (L1, L2 andL3 ). InL1, the pyridine group was directly bonded to an N atom of a carbazole group; while inL2 andL3, the pyridine unit was linked to a benzene group via oxygen and spiro linkages, respectively. The introduction of a heteroatom linkage and spiro linkage into these tetradentate ligands would be effective in breaking the conjugation, leading to a wide bandgap and high E T . Despite the different linkages applied in the pyridine^benzene bidentates, complexesPt1–Pt3 showed similar photoluminescence spectra with an intense emission peak at 460 nm. Organic light-emitting diodes (OLEDs) based on these complexes were fabricated by vacuum deposition with the typical device configuration. All these complexes showed blue electro-phosphorescence at various doping ratios. Among these Pt(ii ) complexes, Pt1 showed the highest OLED performance with a maximum CE, PE, and EQE of 36.5 cd A −1, 33.1 lm W −1, and 16.2%, respectively, with the CIE coordinates of (0.18, 0.32).